Radical Addition of 4-Hydroxyquinazolines and Alkylation of Quinones by the Electro-Induced Homolysis of 4-Alkyl-1,4-dihydropyridines - Luo, Xiaosheng; Feng, Qiping; Wang, Ping (Synthesis, 2022)
The formation of C(sp3)-centered radicals via the electro-induced homolysis of 4-alkyl-1,4-dihydropyridines (alkyl-DHPs) is reported. The resulting alkyl radicals reacted with 4-hydroxyquinazolines or quinones to afford 2-alkyldihydroquinazolinones or alkylated quinones. A broad range of alkyl DHPs could be used as versatile radical precursors under electrolysis conditions. This alterative strategy provided a simple and effective pathway for the construction of C(sp2)–C(sp3) and C(sp3)–C(sp3) bonds under mild conditions.
Keywords: electrochemistry; dihydropyridine; anodic oxidation; radical addition; catalyst-free